Tracking Discharge Delays: Critical First Step Toward Mitigating Process Breakdowns and Inefficiencies. Issue 1 (January 2016) - Holland, Diane E.; Pacyna, Joel E.; Gillard, Kristine L.; Carter, Lisa C.
Abstract : This article reports on the development and evaluation of a mechanism designed for real-time tracking of discharge delays by bedside clinicians and the reporting of delays in a manner amenable to action. During the implementation phase, delay time totaled 23.6 days for 114 patients affected by a delay. More than one-half of delays (61.4%) occurred for patients whose discharge disposition was home to self-care. Abstract : Supplemental Digital Content is Available in the Text.